Burkina Faso : Requests for Disbursement Under the Rapid Credit Facility and Rephasing of Access Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Burkina Faso. (IMF Staff Country Reports; Country Report ;, 2020)
Burkina Faso is facing a security crisis and the COVID-19 pandemic shocks. The number of internally displaced persons (IDPs) has surged nine-fold since January 2019 and is likely to further increase. Access to food and basic services is increasingly difficult for both displaced and host communities. The security crisis is starting to weigh on economic activity and has put the budget under pressure, as security spending is narrowing fiscal space for spending in other priority areas (social, education, health and investment). The global COVID-19 outbreak is worsening the short-term outlook for Burkina Faso further, given the country's limited preparedness and weak health system.